Análise do licenciamento ambiental como instrumento de política do meio ambiente no Rio Grande do Norte Período 1992-2003 - Sousa, Paulo Moraes de (2005)
This analysis on the ambient licensing is based on a research that identifies the fragilities and advances of the application of this instrument of politics of the environment in the ambient politics of the Rio Grande do Norte, in the period of 1992 the 2003. The isolated urban area of Búzios, situated in the City of Nísia Floresta/RN, situated in the eastern coast of the State, where concentrates the boarding of the ambient question as a matter in the Brazilian process of urbanization, over all the institutionalization and implementation of the ambient licensing. They are distinguished in the used methodology in consultation to the diverse involved social segments with the ambient subject in study, the example of the managers, technician and specialists, as well as the application of the legislation and norms techniques, the forms of appropriation of the common wealth and the procedures of ambient licensing of the competent agencies. The results of the research designate that the ambient licensing while instrument of the ambient politics is one of the alternatives more efficient as techniques in the process of sustainable development, since it is beyond the prerogatives to conciliate the activities and enterprises with the conservation of the environmental resources and natural benefits to the societies. In the RN one evidenced progress in the ambient legislation and the instructions techniques, and that the imperfections and limitations in the system of ambient licensing are not directly on to the instruments, but in the implementation of mechanisms of the ambient agencies. This because they do not make use of operational structure to apply in practical and established abilities, as an ambient management, institutional joint and deliberations of the State Counselor for Environment